Analisis Potensi Kota Malang Sebagai Tempat Transit Wisata Kuliner dan Wisata Buatan - Anisa Zuhria Sugeha; Izza Elfaranica; Danny Baskara Wijaya; Dewi Hermin Sutanto (UHN IGB Sugriwa Denpasar, 2023)
Malang City is said to have the potential as a transit city or stopover for tourists both from within and outside the country. The potential of Malang City as a tourist transit city can be utilised in maximising the tourism potential owned by Malang City. Until now, there has been no study or scientific study on the analysis of Malang City as a transit city in maximising other tourism around it. This research is a descriptive qualitative research, the data collection techniques used are interviews with key informants, literature study, and observation. Data from the research results will be analysed using SWOT analysis. The result is that Malang City has great potential as a tourist transit point, with various strengths that can be explored to increase the number of tourist visits. The diversity of attractions, including natural, historical, cultural, and culinary tourism, makes Malang City attractive to various tourist segments. In addition, good transport facilities provide easy accessibility for visitors from various regions. However, there are some challenges that need to be overcome. Dense residential areas, lack of innovation in the development of tourist attractions, and limited facilities for travellers with special needs can reduce Malang City's potential as an attractive tourist transit point. In addition, inadequate road infrastructure, which manifests in traffic congestion on weekends, needs to be improved. To optimise the potential of Malang City as a tourist transit destination, cooperation between the government, the local community, and the private sector is needed so that it can become a more attractive and sustainable tourist transit destination.